The Autobiography of an Ex-Colored Man - Johnson, James Weldon (Saga Egmont, 2022)
James Weldon Johnson\'s emotionally gripping novel is a landmark in black literary history and, more than eighty years after its original anonymous publication, a classic of American fiction.The first fictional memoir ever written by a black person, The Autobiography of an Ex-Coloured Man influenced a generation of writers during the Harlem Renaissance and served as eloquent inspiration for Zora Neale Hurston, Ralph Ellison, and Richard Wright. In the 1920s and since, it has also given white readers a startling new perspective on their own culture, revealing to many the double standard of racial identity imposed on black Americans.Narrated by a mulatto man whose light skin allows him to \"pass\" for white, the novel describes a pilgrimage through America\'s color lines at the turn of the century--from a black college in Jacksonville to an elite New York nightclub, from the rural South to the white suburbs of the Northeast.